Estoques de carbono e nitrogênio e alterações químicas e biológicas na rizosfera em solo com longo histórico de aplicações de diferentes fontes de nutrientes - Santos, Andressa Pinto dos (2023)
The agricultural production system of Brazil is highly dependent on industrialized fertilizers. This work is part of the need to use animal waste as an alternative to the use of industrialized fertilizers, based on knowledge of the long-term impact of these organic residues on the chemical properties and biological and enzymatic activities of the soil, with the aim of to improve both nutrient availability and crop productivity. This Thesis aimed to evaluate the long-term impact of applications of animal manure and mineral fertilizer on corn grain yield and carbon and nitrogen stocks in the soil profile, and investigate chemical and biological changes in the rhizosphere, in soil with long history of applications of different nutrient sources. To this end, we conducted two studies (Chapters 1 and 2) in a long-term experiment, implemented in 2004, under an Typic Hapludalf, in Santa Maria (RS). The treatments used were pig slurry (PS), cattle slurry (CS), pig deep litter (PDL), mineral fertilizer (NPK) and control (no fertilizer application). In Chapter 1, we evaluated the impacts of different types of animal manure and mineral fertilizer on nitrogen and carbon stocks in the soil profile and corn yield after 17 years of application. For this, we collected soil at a depth of 0.50 m, stratifying it in five layers of 0.10 m each, during different corn crop. At the same time, we carry out grain production assessments. In Chapter 2, we selected 3 treatments (liquid swine manure, mineral fertilizer and control) and investigated changes in the chemical characteristics and biological and enzymatic activities as strategies to increase the availability of C and N in rhizospheric corn soils, grown in soil with a history of 17 years of pig slurry and mineral fertilizer applications. For this, we collected rhizospheric and non-rhizospheric soils (bulk soil) of corn, where the activities of the urease and β-glucosidase enzymes, the flux of C and N in the microbial biomass, total organic carbon (TOC), total nitrogen (NT) and soil pH in water. Organic sources provided higher yields of corn grains when compared to mineral fertilizer, with emphasis on pig deep litter and cattle slurry. Furthermore, these same types of manure resulted in a significant increase in TOC and NT stocks only in the most superficial soil layer (0.00-0.10 m) (Chapter 1). On the other hand, we observed that prolonged applications of pig slurry increase the availability of N to the plants, which results from an increase in enzymatic activity (in particular β-glucosidase), TOC, NT, and microbial biomass in the rhizospheric soil. Although the highest pH values were obtained in the control treatment, followed by the application of pig slurry, this did not result in an increase in grain yields in the control soil (Chapter 2). The results of this research suggest that long-term manure applications allow rationalizing or even replacing the use of mineral fertilizers, and also have the potential to sequester C in sandy soils, which is of great importance especially for animal producing regions, where large amounts of waste are produced.